Enforcement of The Principle and Objective of Law Number 5 of Year 1999 on The Prohibition of Monopolistic and Unhealthy Business Competition Practices in Handling Business Competition Cases - Hanif Nur Widhiyanti (Universitas Sebelas Maret, 2024)
One of the cases that the KPPU had ruled on is the case of the suspected violation by PT. Indomarco Prismatama (KPPU Ruling Number 03/KPPU-L-I/2000). In the legal considerations, the KPPU used the principle and objective (Article 2 and Article 3 of Law No. 5 of Year 1999) as the juridical foundation. This situation appears to be special in the history of rulings made by a Council in Indonesia. Usually, violations are only considered to occur upon the execution of forbidden acts for which the elements of the acts have been stated clearly according to the article formulations of a certain Law. This research used the normative juridical approach. This research is a case study of KPPU Ruling Number 03/KPPU-L-I/2000 on the Suspected Violation of the Prohibition of Monopolistic and Unhealthy Business Competition Practices by PT. Indomarco Prismatama. From the research results, it can be concluded that there is a discrepancy with what is idealized (das sollen) by Law No. 5 of Year 1999, and thus the enforcement process for Law No. 5 of Year 1999 returns to the basic function of the formation of the Law, which is to unite ideal and real factors. Although textually the articles that are suspected to be committed by the Respondent cannot be proven, to achieve the ideals of Law No. 5 of Year 1999, the substance of Article 2 and Article 3 may become the foundation to evaluate whether the business activities conducted by the Respondent can be declared to violate Law No. 5 of Year 1999, whether by the concrete legal regulation or the principle and objective of formation of Law No. 5 of Year 1999. As the sanctions that are imposed by the KPPU must agree with the objective of the creation of Law No. 5 of Year 1999, in relation to the Indomaret case, the KPPU ruling is expected to be able to alter the behavior of the Respondent who did not pay sufficient attention to competitive balance, which is realized in the form of several kinds of sanctions as specified in the KPPU Ruling.